THE INFLUENCE OF WEIGHT-LOSS STRATEGIES ON THE PHYSICAL AND FUNCTIONAL READINESS OF KARATEKAS (American Journal of Pedagogical and Educational Research, 2023)
This article analyzes the impact of weight-loss strategies on the physical and functional fitness of karatekas in the discipline of kumite. The prevalence and classification of rapid weight loss (RWL) strategies are examined, as well as the main physiological mechanisms of their impact on athletes' performance. It is shown that dehydration and depletion of energy substrates are key factors in the reduction of strength and speed-strength indicators, and even moderate weight loss (≈2%) can negatively impact the competitive effectiveness of karatekas. The advisability of prioritizing gradual weight management and limiting aggressive weight-loss practices is substantiated.